2021
DOI: 10.3390/microorganisms9102120
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Beyond: Exploring Public Health Benefits from Non-Specific Effects of BCG Vaccination

Abstract: Bacille Calmette–Guérin (BCG) vaccination, widely used throughout the world to protect against infant tuberculous meningitis and miliary tuberculosis (TB), can provide broad non-specific protection against infectious respiratory diseases in certain groups. Interest in BCG has seen a resurgence within the scientific community as the mechanisms for non-specific protection have begun to be elucidated. The impact of the COVID-19 pandemic on nearly every aspect of society has profoundly illustrated the pressure tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 168 publications
(187 reference statements)
0
7
0
Order By: Relevance
“…This includes a multicenter US study: ClinicalTrials.gov Identifier: NCT04348370. The large data sets associated with COVID-19 vaccines will undoubtedly be mined for years to come including the role that BCG may have had with COVID-19 [47].…”
Section: Discussionmentioning
confidence: 99%
“…This includes a multicenter US study: ClinicalTrials.gov Identifier: NCT04348370. The large data sets associated with COVID-19 vaccines will undoubtedly be mined for years to come including the role that BCG may have had with COVID-19 [47].…”
Section: Discussionmentioning
confidence: 99%
“…50 Other studies found that increased rates of BCG vaccination by country were correlated with slower rates of COVID-19 infection in the population, although many factors may confound the relationship. 51 Of note, a heat-killed strain of Mycobacterium (Mycobacterium w.) can be used as an immunomodulator and was injected as adjuvant therapy for COVID-19 infection with some associated clinical benefit. 52 However, cutaneous infection and ulceration was a common side effect.…”
Section: Mycobacteria and Covid-19mentioning
confidence: 99%
“…For instance, the current BCG Pasteur differs from the original Pasteur strain by polymorphisms and deletions. BCG strains are used both as a vaccine to prevent TB and as an immunotherapy of bladder cancer [57,121]. In addition, there is active research on the use of BCG to treat other cancers and non-infectious diseases, such as autoimmune disorders and type I diabetes [122].…”
Section: Mycobacterium Bovis Bcgmentioning
confidence: 99%
“…Subsequent observational studies in children in West Africa demonstrated that BCG vaccination decreases morbidity due to infections other than TB, including malaria [54,55]. Very recently, epidemiological studies indicated that TI induced by BCG could be protective against the development of severe coronavirus disease 2019 in humans [56,57]. Strikingly, studies performed in the 1970's showed that BCG inoculation protects mice against lethal experimental infection with B. microti and Plasmodium berghei [58,59].…”
Section: Introductionmentioning
confidence: 99%